Estimation of global case fatality rate of coronavirus disease 2019 (COVID-19) using meta-analyses: Comparison between calendar date and days since the outbreak of the first confirmed case. (November 2020) - Ghayda, Ramy Abou; Lee, Keum Hwa; Han, Young Joo; Ryu, Seohyun; Hong, Sung Hwi; Yoon, Sojung; Jeong, Gwang Hun; Lee, Jinhee; Lee, Jun Young; Yang, Jae Won; Effenberger, Maria; Eisenhut, Michael; et al.
Highlights: Estimating the coronavirus disease 2019 (COVID-19) pandemic's case fatality rate (CFR) has been the focus and interest of many stakeholders as it plays a key role in understanding this pandemic and guides appropriate responses and efficient mitigation strategies. The traditional cumulative CFR estimation is static; however, it is a dynamic value. Moreover, the estimation of the global CFR of COVID-19 according to either the calendar date or the days since the outbreak of the first confirmed case, is different. We propose that the estimated kinetics of CFR according to days since the outbreak of the first confirmed case could be a useful predictor to design COVID-19 mitigation strategies. Abstract: Objective: Since the outbreak of the coronavirus disease 2019 (COVID-19) in December of 2019 in China, estimating the pandemic's case fatality rate (CFR) has been the focus and interest of many stakeholders. In this manuscript, we prove that the method of using the cumulative CFR is static and does not reflect the trend according to the daily change per unit of time. Methods: A proportion meta-analysis was carried out on the CFR in every country reporting COVID-19 cases. Based on these results, we performed a meta-analysis for a global COVID-19 CFR. Each analysis was performed using two different calculations of CFR: according to the calendar date and according to the days since the outbreak of the first confirmed case. We thus explored an innovative and original calculation of CFR, concurrently based on the date of the first confirmed case as well as on a daily basis. Results: For the first time, we showed that using meta-analyses according to the calendar date and days since the outbreak of the first confirmed case, were different. Conclusion: We propose that a CFR according to days since the outbreak of the first confirmed case might be a better predictor of the current CFR of COVID-19 and its kinetics.